Politik Hukum Islam Dalam Pelaksanaan Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Syariah Di Indonesia - Wahid, Sahid; Aisyah, Siti; Sakka, Abdul Rahman (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
Indonesia as a country with a Muslim majority population has significant demand for financial and insurance services that are in accordance with Sharia principles. Therefore, it is important for the social security sector to participate in adopting Sharia principles in order to provide services that are more in accordance with Islamic values embraced by the majority of the Indonesian population. BPJS Ketenagakerjaan as one of the institutions responsible for providing social protection for workers has the task and function to organize social security for workers through a program. The integration of Sharia principles in BPJS Ketenagakerjaan is not just a cosmetic change or adjustment of terminology, but involves fundamental changes in the way this institution operates. The research method used is qualitative research, the implications of this method are descriptive analytical. The approach used by researchers in solving existing problems is normative juridical. The results of this study indicate that there is potential for the development of BPJS Ketenagakerjaan with the application of Islamic Sharia principles. the concept of social security that combines the values of humanity, justice, and sharia has great potential to provide effective and sustainable protection for people in need, as well as strengthen the moral and ethical foundations in social and economic development.